2019
DOI: 10.15171/apb.2019.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cultivation Condition and Media Content on Chlorella vulgaris Composition

Abstract: Microalgae are a source material in food, pharmacy, and cosmetics industries for producing various products including high-protein nutritional supplements, synthetic pharmaceuticals, and natural colors. A promising algal source for such productions is Chlorella vulgaris which contains a considerable protein content. Similar to other microalgae, its desirability is minimal nutrient requirements since they are unicellular, photosynthetic, and fast-growing microorganisms. Another propitious option to be produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 89 publications
(96 reference statements)
0
20
1
1
Order By: Relevance
“…It is noteworthy that this trend in carotenoid accumulation differs from the widely reported stress-induced accumulation by many microalgae species (Koyande et al 2019 ; Novoveska et al 2019 ; Panahi et al 2019 ). A possible explanation to this trend of carotenoid accumulation might be that different regulatory mechanisms of carotenoid biosynthesis function in these species (Pribyl et al 2016 ).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…It is noteworthy that this trend in carotenoid accumulation differs from the widely reported stress-induced accumulation by many microalgae species (Koyande et al 2019 ; Novoveska et al 2019 ; Panahi et al 2019 ). A possible explanation to this trend of carotenoid accumulation might be that different regulatory mechanisms of carotenoid biosynthesis function in these species (Pribyl et al 2016 ).…”
Section: Resultscontrasting
confidence: 63%
“…Use of efficient photobioreactors to enhance growth rates and productivities (Huang et al 2017 ); and 3. Manipulation of cultivation conditions, which currently involves the use of stressed conditions as widely reported in literature (Koyande et al 2019 ; Mussagy et al 2018 ; Novoveska et al 2019 ; Panahi et al 2019 ). In terms of selection of species/strains for production of pigments, few microalgae species which include but not limited to Dunaliella sp., Porphydrium sp., and Spirulina sp.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is needed for the formation of protein (the building blocks of the cell) and nucleic acid, while phosphor (in the form of phosphate) is part of the backbone of DNA and RNA, which are genetic materials that essential for the human life (Juneja et al, 2013). Furthermore, research showed that the increase of nitrate (NO3) utilization would increase the protein content by up to 44.3% (Panahi et al, 2019). That is why the biomass production in Walne's is higher than in Guillard's medium due to the wide difference in N and P concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Different growth conditions, such as temperature, nutrient composition, and light availability, can readily alter the levels of biomass, macro- and micronutrients, and other valuable bioactive compounds, including antioxidants, in Chlorella cells [ 28 , 29 , 30 ].…”
Section: Nutrients In Commercial Chlorella Prodmentioning
confidence: 99%